Assessment of the Mechanical Strengths of the Concretes from the Joints Between the Precasted Wall Panels Subjected on Dissolving – Levigation Corrosion. (2016) - Diaconu, Livia Ingrid; Plian, Diana
Abstract: The proposed testing technology joins the advanced research technologies and allows the development of the concretes technologies for other working conditions. The assessment of the mechanical characteristics of the concrete from the joints cannot be realized by usual procedures (ultrasounds, recoil etc.). The mechanical strengths from the concrete wall panels' joints represents an important issue for the experts. In the concrete from the panels joints the type I corrosion process is occurring as a consequence of the sweat because the most of the times the joints represent thermal bridges. The corrosion process represents the single responsible for the concrete's from the joints structural modifications, removing the gelivity degradation idea because the necessary optimal humidity of this process is not realized.